DESIGN AND DEVELOPMENT OF A WEB-BASED POSYANDU APPLICATION USING THE WATERFALL METHOD - Septianita; Ardianto, Darmawan; Juliansyah, Yahya Maulana; Ramayanti, Desi (Cattleya Darmaya Fortuna, 2023)
The Integrated Service Post (Pos Pelayanan Terpadu or POSYANDU) is a monthly activity center aimed at monitoring toddlers under five years old. The Posyandu Application plays a vital role in public service due to its ability to simplify complex tasks and reduce the time required for tasks that were once time-consuming. The aim of this research is to implement an application to regularly monitor the growth and nutritional intake of toddlers. As its execution is still manual, Posyandu cadres face difficulties in data retrieval and recording similar names in different formats. Moreover, mothers find it challenging to monitor their children's growth solely through the Posyandu book, as in this modern era, they are more inclined towards using gadgets rather than reading books. This research applies the waterfall method, a development model following the classic life cycle. This method employs sequential and systematic phases, along with Blackbox testing for system validation. The research results in a Posyandu data processing application that supports reporting services for child growth and development at Posyandu. Furthermore, the application facilitates parents or mothers in presenting information for monitoring their children's immunization.